A stochastic modelling framework for predicting flexural properties of ultra-thin randomly oriented strands - Xu, Xiaodong; Jesus, André; Wan, Yi; Takahashi, Jun (Taylor & Francis, 2025)
A stochastic modelling framework is developed to predict the flexural properties of high-strength sheet moulding compounds made of randomly oriented ultra-thin carbon fibre-reinforced thermoplastic prepreg tapes. The model enables reliable designs using ultra-thin randomly oriented strands with less testing, leading to potential applications in automotive primary structures. The stochastic model is based on a Monte Carlo simulation. The flexural modulus is predicted using classical laminate theory, while the flexural strength is predicted by following a Weibull distribution. Fibre discontinuities are considered through stress concentrations introduced by tape overlaps. The results are validated against new 3-point bending and previously reported 4-point bending experimental results. A scaling effect on strength and scatter is predicted, and its implications for structural applications are also discussed.
Keywords: strength; moulding compounds; thin ply; thermoplastics; randomly oriented strands